Gene Profiling of Nucleus Basalis Tau Containing Neurons in Chronic Traumatic Encephalopathy: A Chronic Effects of Neurotrauma Consortium Study - Mufson, Elliott J. (J Neurotrauma, 2018)
Military personnel and athletes exposed to traumatic brain injury may develop chronic traumatic encephalopathy (CTE). Brain pathology in CTE includes intracellular accumulation of abnormally phosphorylated tau proteins (p-tau), the main constituent of neurofibrillary tangles (NFTs). Recently, we found that cholinergic basal forebrain (CBF) neurons within the nucleus basalis of Meynert (nbM), which provide the major cholinergic innervation to the cortex, display an increased number of NFTs across the pathological stages of CTE. However, molecular mechanisms underlying nbM neurodegeneration in the context of CTE pathology remain unknown. Here, we assessed the genetic signature of nbM neurons containing the p-tau pretangle maker pS422 from CTE subjects who came to autopsy and received a neuropathological CTE staging assessment (Stages II, III, and IV) using laser capture microdissection and custom-designed microarray analysis. Quantitative analysis revealed dysregulation of key genes in several gene ontology groups between CTE stages. Specifically, downregulation of the nicotinic cholinergic receptor subunit β-2 gene (CHRNB2), monoaminergic enzymes catechol-O-methyltransferase (COMT) and dopa decarboxylase (DDC), chloride channels CLCN4 and CLCN5, scaffolding protein caveolin 1 (CAV1), cortical development/cytoskeleton element lissencephaly 1 (LIS1), and intracellular signaling cascade member adenylate cyclase 3 (ADCY3) was observed in pS422-immunreactive nbM neurons in CTE patients. By contrast, upregulation of calpain 2 (CAPN2) and microtubule-associated protein 2 (MAP2) transcript levels was found in Stage IV CTE patients. These single-population data in vulnerable neurons indicate alterations in gene expression associated with neurotransmission, signal transduction, the cytoskeleton, cell survival/death signaling, and microtubule dynamics, suggesting novel molecular pathways to target for drug discovery in CTE.